Workplace spirituality and employee engagement: an empirical analysis. (14th March 2022) - Baskar, B.; Indradevi, R.
Workplace spirituality (WPS) is a prominent topic gaining appreciation and value among academicians and industry experts. WPS aims at meaningful work, sense of community, and value of organisation. Spirituality in the workplace involves the effort to find out one's ultimate purpose in life, to develop a strong connection with co-workers and other people associated with work, and to have consistency (or alignment) between one's core beliefs and their organisation's values. This study investigates spirituality in the workplace and attempts to examine the relationship on how the concept and practice of workplace spirituality influences employee engagement in non-governmental organisations. The respondents were the employees from selected NGOs. The study has established that WPS has a direct effect on employee engagement. The study provides new insights to the NGO employees, for effective engagement to their social work through the spiritual virtues at workplace.